2018
DOI: 10.1021/acsami.8b00845
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Ultrathin Native Oxides on III–Nitride Surfaces

Abstract: When pristine material surfaces are exposed to air, highly reactive broken bonds can promote the formation of surface oxides with structures and properties differing greatly from bulk. Determination of the oxide structure is often elusive through the use of indirect diffraction methods or techniques that probe only the outermost layer. As a result, surface oxides forming on widely used materials, such as group III-nitrides, have not been unambiguously resolved, even though critical properties can depend sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Recently, Dycus et al have revealed the structure of ultrathin oxides that form on AlN surfaces by experiment . There are some similarities between our simulated structures and the experimental results, as shown in Figure S3.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Recently, Dycus et al have revealed the structure of ultrathin oxides that form on AlN surfaces by experiment . There are some similarities between our simulated structures and the experimental results, as shown in Figure S3.…”
Section: Resultssupporting
confidence: 80%
“…However, there are many metastables, the so-called "transition alumina" structures exiting, one of which is cubic γ-Al 2 O 3 . 33 In this study, γ- 6 There are some similarities between our simulated structures and the experimental results, as shown in Figure S3. In…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Although several reports on surface treatment have been published, it is difficult to remove this oxide layer completely using ordinary solutions [22][23][24][25][26][27] . Recently, it has been reported that the surface oxide layer formed by long-term air exposure after specific chemical treatments has a crystalline nature [28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, on one hand, such vertical and high-aspect-ratio geometry (1) enables core-shell device architecture in the radial direction which facilitates efficient light absorption and photo-generated charge-carrier extraction for high-efficient photovoltaic or photodetection applications 17,18 , and (2) provides high density of surface sites for artificial photosynthesis or photoelectrochemical photodetection [19][20][21][22] . On the other hand, ultrahigh surface areas naturally induce a high density of surface states 23,24 , which could act as charge trapping centers and harmful to the performance of nanoscale devices. Thus, effective surface passivation approaches are then required to remove or suppress such surface states to boost nanowire device performance 25 .…”
Section: Introductionmentioning
confidence: 99%